Domination and independence numbers of large 2-crossing-critical graphs - Iršič, Vesna (Ars mathematica contemporanea, 2023)
After 2-crossing-critical graphs were characterized in 2016, their most general subfamily, large 3-connected 2-crossing-critical graphs, has attracted separate attention. This paper presents sharp upper and lower bounds for their domination and independence number.
Keywords: crossing-critical graphs; dominantno število; domination number; independence number; neodvisnostno število; prekrižno-kritični grafi